A P‐THMC Model to Solidification and Solute Separation in Saturated Freezing Soil - Xiaojie Mo; Dongsheng Zhang; Feiyuan Ge; Huan Huang; Changfu Chen; Mingzhu Liu; Honghan Chen (Water Resources Research, 2025)
Abstract The salt distribution of freezing saturated soil is a dynamic thermo‐hydraulic‐mechanical‐chemical (THMC) interaction process. Freezing‐induced solute separation, a process strongly influenced by solute type, is often neglected in THMC models. Based on phase diagram, we obtained the freezing point at different concentrations and the eutectic point, the lowest temperature at which freezing can occur. The evolution of the order parameter, which denotes the state of water (ice or liquid) in the phase‐field model, is mathematically correlated with the solidification line. We further propose a phase‐field‐THMC (P‐THMC) model that incorporates solute separation to simulate water transfer, soil particle movement and solute migration during the freezing process. Then, the P‐THMC is solved using FlexPDE, a finite element model builder for partial differential equations. The model's validity and utility are demonstrated through comparison with two experimental results. The study provides a theoretical framework for pollution migration and distribution research in seasonal frozen area, freezing concentration in food industry and cell conservation in pharmaceutical industry.